2018
DOI: 10.1016/j.eururo.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentre Study of 5-year Outcomes Following Focal Therapy in Treating Clinically Significant Nonmetastatic Prostate Cancer

Abstract: BackgroundClinically significant nonmetastatic prostate cancer (PCa) is currently treated using whole-gland therapy. This approach is effective but can have urinary, sexual, and rectal side effects.ObjectiveTo report on 5-yr PCa control following focal high-intensity focused ultrasound (HIFU) therapy to treat individual areas of cancer within the prostate.Design, setting, and participantsThis was a prospective study of 625 consecutive patients with nonmetastatic clinically significant PCa undergoing focal HIFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
206
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(230 citation statements)
references
References 33 publications
16
206
4
4
Order By: Relevance
“…An overview of HIFU studies is presented in Table 5. For focal HIFU or HIFU hemiablation, UTI rates range between 5.6 and 17.9% [1,5,11,16,17]. Only the trial by Ahmed et al [11] reported in more detail on perioperative antibiotic treatment using prophylaxis with gentami-cin or targeted therapy in addition to a fluoroquinolone therapy for 7 days post treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of HIFU studies is presented in Table 5. For focal HIFU or HIFU hemiablation, UTI rates range between 5.6 and 17.9% [1,5,11,16,17]. Only the trial by Ahmed et al [11] reported in more detail on perioperative antibiotic treatment using prophylaxis with gentami-cin or targeted therapy in addition to a fluoroquinolone therapy for 7 days post treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Organ-sparing focal therapies of localized prostate cancer aim to efficiently treat intraprostatic cancer lesions and to avoid side effects of whole gland treatments. There is a growing body of studies presenting oncological and functional outcomes for patients treated with experimental therapies such as high-intensity focused ultrasound (HIFU) [1][2][3][4]. However, when reporting adverse events, studies commonly focus on those events affecting genitourinary function, which are voiding, continence, and potency.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is the fifth leading causes of cancer-related death and the most common human carcinoma among men worldwide [1]. Androgen deprived therapy (ADT) or platinum-based chemotherapy or other systemic treatment has been proved to partial effectively to alleviate symptoms for advanced prostate adenocarcinoma patients; however, the overall survival benefit is still limited [2]. A growing number of evidence highlights that exceptional overexpression of apoptosis resistant proteins, and dysregulation of proliferation-related genes is obsessed in the advance of PCa [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Both preclinical and clinical results have demonstrated clinical efficiency of direct ablation and treatment by HIFU in areas such as prostate cancer, uterine fibroids, breast cancer, thyroid cancer, bone metastasis, essential tremor, brain tumors, pancreas cancer, and liver cancer . In these applications, HIFU systems are often combined with magnetic resonance imaging systems (MR) as integrated therapeutic systems, with MR guiding the positioning of the HIFU focal point in the organ being target for treatment, so‐called magnetic resonance‐guided focused ultrasound (MRgFUS).…”
Section: Introductionmentioning
confidence: 99%